C-H activation of methane to syngas on MnxCe1-x-yZryO2 - a molecular beam study - Dubey, Anjani; Kolekar, Sadhu K.; Gopinath, Chinnakonda S. (Chemcatchem, 2016)
Mn-doped ceria zirconia thin films (MnxCe1-x-yZryO2, MCZ) were employed as flat model catalyst surfaces for CH4 activation. MCZ films exhibit characteristics of single crystal and powder materials, such as smooth surfaces and porosity. From molecular-beam studies, it has been identified that the oxygen storage capacity increases with Mn content. Mutually exclusive observation of H2O or a mixture of products (CO2+ CO + H-2) occurs, when the reactants was allowed to react directly on MCZ, underscoring their formation or prevention (and consumption), respectively. The results suggest that there is competition and cooperation among different elementary reactions under complementary conditions. From a significant partial oxidation of CH4 through C-H activation, it is found that formation of syngas begins at 700 K and the reaction rate increases with increasing temperature. Kinetic evidences indicate that the reaction proceeds through a combustion-reformation pathway.